Core competencies in disaster management for social workers in China: A modified e-Delphi study. (July 2023) - Sim, Timothy; He, Minying
Summary : A modified e-Delphi study was conducted to identify the core competencies required by social workers for disaster management in China. A list of competencies was compiled through an integrative review and in-depth interviews. We then conducted a three-round e-Delphi survey with 25 experts including social work practitioners and academics, government officials and other professionals. After a 4-month period of data collection and analysis, we proposed a specific social work competence framework for disaster management in the unique context of China. Findings : A total of 87 competencies were identified and categorised into knowledge, values and skills needed for the mitigation, preparedness, response and recovery phases of disaster management (a total of 15 categories). Through a further thematic analysis, we identified four interconnected themes related to disaster resilience building and social justice in various phases. Applications : This ground-breaking competence framework can inform Chinese social work practice and training in disaster management, thus enabling social workers to better identify their specific professional roles and tasks in disaster contexts. The framework can also enhance transdisciplinary collaboration among social workers and the various disaster management stakeholders, and can also be of value when developing social work core competencies outside of China.